2012
DOI: 10.1371/journal.pone.0029887
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Renal Ischemia-Reperfusion Injury Is Unchanged in AMPK-β1 Deficient Mice

Abstract: AimActivation of the master energy-regulator AMP-activated protein kinase (AMPK) in the heart reduces the severity of ischemia-reperfusion injury (IRI) but the role of AMPK in renal IRI is not known. The aim of this study was to determine whether activation of AMPK by acute renal ischemia influences the severity of renal IRI.MethodsAMPK expression and activation and the severity of renal IRI was studied in mice lacking the AMPK β1 subunit and compared to wild type (WT) mice.ResultsBasal expression of activated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…These results are in line with Mount et al (2012) and Chen et al (2012). Furthermore, Kadkhodaee et al (2009) reported that the rise of renal injury markers was dependent on the renal ischemia time, and Jung et al (2009) found the increase in renal injury markers reached the peak 48 hours after the renal I/R injury.…”
Section: Discussionsupporting
confidence: 83%
“…These results are in line with Mount et al (2012) and Chen et al (2012). Furthermore, Kadkhodaee et al (2009) reported that the rise of renal injury markers was dependent on the renal ischemia time, and Jung et al (2009) found the increase in renal injury markers reached the peak 48 hours after the renal I/R injury.…”
Section: Discussionsupporting
confidence: 83%
“…Rabbit antibodies directed against pNKCC1 (T212/217)/ pNKCC2 (T96/T101), pNKCC2 (S126), and pNCC (T58) have previously been described (10). Rabbit antibodies against AMPK-␣ and pACC1 (S79) have previously been described (33,50). Mouse antibody against NKCC1/NKCC2 (T4) was obtained from the Developmental Studies Hybridoma Bank (University of Iowa).…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies directed against AMPK-␣1, AMPK-␣2, AMPK phospho-Thr 172 , and ACC1 phospho-Ser 79 have previously been described (20,42,55). Rabbit antibodies against NKCC2, Na ϩ -Cl Ϫ cotransporter (NCC), and the ␤-subunit of ENaC (ENaC-␤) were obtained from StressMarq Biosciences.…”
Section: Methodsmentioning
confidence: 99%
“…Kidneys were excised rapidly and snap frozen in liquid nitrogen as previously described (42). Lysates were prepared using a glass on glass Dounce homogenizer in lysis buffer [containing 50 mM Tris·HCl (pH 7.5), 1 mM EGTA, 1 mM EDTA, 50 mM sodium fluoride, 5 mM sodium pyrophosphate, 1 mM sodium orthovanadate, 1% (wt/vol) Nonidet P-40, 0.27 M sucrose, and 0.1% (vol/vol) 2-mercaptoethanol].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation